Institutional Pesantren in the Coil of Kurnas and Divine Mission - Suharyat, Yayat; Khoirunnisa, Siti (International Journal of Global Sustainable Research, 2023)
Research explores the institutional role of Islamic boarding schools in developing "Kumparan Kurnas" and fulfilling their divine mission. Using a qualitative approach, the study analyzes the internal dynamics of the Islamic boarding schools, particularly in managing and implementing "Kumparan Kurnas," as well as how they understand and actualize their divine mission. Results indicate that Islamic boarding schools are not merely traditional educational institutions but also function as spiritual and cultural centers. "Kumparan Kurnas," as a form of institutional development, serves as a means to support the sustainability of Islamic boarding schools in fulfilling their divine mission. The involvement of stakeholders, including students, kyai (teachers), and the local community, also plays a crucial role in the successful implementation.